2001
DOI: 10.1097/00000539-200105000-00027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prone Positioning on Intraabdominal Pressure and Cardiovascular and Renal Function in Patients with Acute Lung Injury

Abstract: Prone positioning is increasingly used to improve gas exchange in patients with acute lung injury. However, during prone positioning an increase in intraabdominal pressure in these critically ill patients may promote dysfunction of other organs. Therefore, we performed a randomized study in mechanically ventilated patients with acute lung injury to investigate the cardiovascular and renal effects of prone positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 22 publications
6
73
0
4
Order By: Relevance
“…Michelet et al 139 reported that air-cushioned mattresses (vs foam mattresses) prevented an increase in IAP and preserved hepatic perfusion but had no impact on hemodynamics, extravascular lung water, or pulmonary gas exchange. Hering et al 140 found that air-cushioned mattresses without abdominal support caused IAP to increase by 2 mm Hg, coinciding with a small increase in cardiac index that maintained adequate renal function.…”
Section: Hemodynamic Effects Of Iap During Ppmentioning
confidence: 99%
“…Michelet et al 139 reported that air-cushioned mattresses (vs foam mattresses) prevented an increase in IAP and preserved hepatic perfusion but had no impact on hemodynamics, extravascular lung water, or pulmonary gas exchange. Hering et al 140 found that air-cushioned mattresses without abdominal support caused IAP to increase by 2 mm Hg, coinciding with a small increase in cardiac index that maintained adequate renal function.…”
Section: Hemodynamic Effects Of Iap During Ppmentioning
confidence: 99%
“…Unsupporting the abdomen likely decreased intraabdominal pressure (potentially creating negative intraabdominal pressure), reduced the pressure gradient across the diaphragm, and promoted alveolar recruitment preferentially in the dorsal regions of this surfactant-deficient model of lung injury. However, the prone position has also been shown to improve gas exchange when the abdomen was resting on a surface (33)(34)(35). Furthermore, the effect of unsupporting the abdomen in the prone position may depend on the pathophysiology of the injury: unsupporting the abdomen may promote alveolar recruitment and more uniform lung aeration in the presence of atelectasis and alveolar collapse, but it may be ineffective in the presence of alveolar consolidation or flooding, as in the oleic acid model (36).…”
Section: Effect Of the Prone Position On Regional Perfusion Shunt Amentioning
confidence: 99%
“…Correlations have been seen between elevated IAP and prone position with spine surgery. 7,14,20 Three of 4 patients experiencing abdominal complications in this series were obese. With obese patients, the IAP is elevated compared with those with a normal BMI.…”
Section: Discussionmentioning
confidence: 74%